A vision for IMF surveillance - Robert Lavigne; Philipp Maier; Eric Santor (Bank of Canada, 2007)
The ongoing review of the IMF, initiated in 2005 by Managing Director De Rato, presents an excellent opportunity to re-examine the role, functions and governance of the Fund. In particular, the objective, scope and conduct of IMF surveillance have been identified as a key area for renewal. In this paper, we offer a new vision for IMF surveillance. There are two main parts to our proposal. First, we develop Guidelines for Economic Policy Frameworks” that outline the objective and scope of surveillance. They delineate the benchmarks against which members economic policy frameworks can be assessed. The Guidelines also serve to clarify the principles under which surveillance is conducted, and reaffirm members' commitments to the surveillance process under their Article IV obligations. The second element of our proposal is a Surveillance Remit”. The Remit defines the aim of surveillance and the obligations of the Fund to pursue this goal. As such the Remit creates a mechanism to hold the Fund accountable. An important implication of the Remit is that it requires the Fund to become more independent in its day-to-day operations. In addition, we propose procedures for communicating surveillance and for assessing the Fund's conduct of surveillance. Taken together, the various elements reinforce each other, providing a clear role for the IMF, as well as its member countries, in the surveillance process. This principles-based approach can bolster the credibility and legitimacy of surveillance, and ultimately its effectiveness, to the benefit of all members.
Keywords: F33; 330; International topics; Financial stability; Internationaler Finanzmarkt; Internationale Wirtschaftsbeziehungen; Internationale Wirtschaftsorganisation